The long-run labor-market consequences of civil war: Evidence from the Shining Path in Peru - Jose Galdo (Institute for the Study of Labor (IZA), 2010)
This study exploits district-level variation in the timing and intensity of civil war violence to investigate whether early-life exposure to civil wars affects labor-market outcomes later in life. In particular, we examine the impacts of armed conflict in Peru, a country that experienced the actions of a tenacious, brutally effective war machine, the Shining Path, between 1980 and 1995. This study finds that the most sensitive period to early-life exposure to civil war violence is the first 36 months of life. A one standard deviation increase in civil war exposure leads to a four percent fall in adult monthly earnings. Neither fetal, nor pre-school, periods significantly affect long-run earnings. Substantial heterogeneity in the earnings impacts emerge when considering variation in the types of civil war violence. Sexual violations disproportionally affected the wages of women, while torture and forced disappearances disproportionally affected the wages of men. Evidence on intervening pathways suggests that health rather than schooling is the most important channel in connecting early-life exposure to civil war and adult earnings.
Keywords: I12; J13; O12; O15; 330; Civil war; earnings; measurement error; instrumental variable approach; Shining Path; Bürgerkrieg; Wirkungsanalyse; Gesundheit; Einkommen; Erwerbsverlauf; Schätzung; Peru